THE METHODOLOGICAL BASIS OF SAFETY OF HUMAN LIFE - I. M Chizh; V. G. Bazhenov (Сеченовский вестник)
The introduction of a system of general and vocational education philosophy, methods, means and forms of human interaction with the environment is one of the ways to improve the safety of life.The basic terms and concepts: livelihoods and vital functions of man, the danger to life and health, pathogenic situation, risk factors, health and disease are viewed from the standpoint of biology and psychology. A classification of environmental factors based on the results of the influence on the human body is given according to its composition and nature.Creating a favorable environment and rational use of available means of protection depends on the level of safety culture of the population.